Pelatihan Inovasi Kuliner dan Pengembangan Menu di Destinasi Wisata Pemancingan Wong Dheso - Mashudi Mashudi; Ida Rahayu; Henricus Yayan Setyanto (Jurnal Pemberdayaan Masyarakat, 2025)
According to 2024 data from the Central Bureau of Statistics (BPS), Bintan Regency recorded a 238.79% increase in tourist visits compared to the previous year. Pemancingan Wong Dheso spot is among the potential destinations for further development, especially in local culinary tourism. However, challenges remain, including unstructured menus, inconsistent food pricing, poor presentation, and limited use of local agricultural and fishery products. This community service program aimed to enhance the capacity of local culinary managers in structuring menus, improving food presentation, and utilizing local ingredients to strengthen the region’s culinary identity. A participatory and hands-on approach was used, including workshops, Focus Group Discussions (FGDs), and direct mentoring. The training involved 20 participants and resulted in improved culinary skills, development of buffet and à la carte menus, and better standardization of restaurant operations. Participant satisfaction scored 5.0 in practical sessions, 4.7 in perceived benefits, and 4.5 in overall satisfaction. The results indicate that this training model is effective, practical, and adaptable. It also presents a replicable strategy for developing culinary tourism based on local resources and community empowerment in rural destinations.